Digital solutions to promote nutritious foods: Value chains for biofortified staples - Walton, Jenny; Aytekin, Destan (United Nations Systems Standing Committee on Nutrition, 2020)
Micronutrient (mineral and vitamin) deficiency is one of the three forms of malnutrition, alongside overweight or obesity and undernutrition. It affects more than 2 billion people globally, causing health problems, reducing productivity and curtailing income at individual and national level (IFPRI, 2016). Malnutrition, in all its forms, can be tackled with a healthy diet. Current food systems are unable to provide healthy diets for many, however, especially those in rural areas who cannot access or afford nutrient-dense foods and rely on staple crops for their calorific needs. The biofortification of staples commonly grown and consumed in lower- and middleincome countries (LMICs) with key micronutrients (such as vitamin A, iron and zinc) is a cost-effective and scalable strategy with proven potential to improve the micronutrient access of the population (Lockyer, White and Butriss, 2018; HarvestPlus, 2019; Bouis and Saltzman, 2017).